The book of revolutions : the battles of priests, prophets, and kings that birthed the Torah - Feld, Edward, 1943- (University of Nebraska Press ; Jewish Publication Society, 2022)
"The Book of Revolutions unveils the epic saga of ancient Israel as the visionary legacy of inspired authors in different times and places, and the Torah as an emblem of pluralistic belief born of three revolutionary moments in history"--